Endogenous and exogenous fluorescence diagnosis of tumors in the lower part of the gastrointestinal tract. Issue 1 (March 2021) - Genova, Ts.; Valkov, H.; Vladimirov, B.; Kolev, B.; Angelov, I.; Avramov, L.; Borisova, E.
Abstract: Endogenous fluorescence measurements using UV-VIS excitation wavelengths revealed a variety of natural fluorophores, including the amino acids tyrosine and tryptophan, coenzymes – NADH and flavin, collagen and elastin. Deep minima in the tumor fluorescence signals were observed in the region 540 – 575 nm related to re-absorption of hemoglobin. Such high haemoglobin content was also found as an indication of the tumor's vascularization and it was clearly pronounced in all dysplastic and tumor sites investigated ex vivo . A photosensitizer from the family of porphyrins was applied as an exogenous fluorescent marker, namely, delta-aminolevulinic acid/protoporphyrin IX (5-ALA/PpIX). The 5-ALA was administered per os six hours before endoscopic observation and spectral measurements at a dose of 20 mg/kg. A high-power light-emitting diode at 405 nm was used as an excitation source (LED-405, 25 mW, CW, Polironik Ltd., Russia). A fiber was introduced through an endoscopic instrumental channel in order to retrieve information about the fluorescence to a USB4000 micro-spectrometer (OceanOptics Inc., Dunedin, USA). The fluorescence detected from in vivo tumor sites has very complex spectral origins. It consists of autofluorescence, fluorescence from exogenous fluorophores and re-absorption from the chromophores accumulated in the investigated tissue. However, the fluorescence of 5-ALA/PpIX was clearly pronounced in the 630 – 710 nm region, having a significant contrast with the surrounding normal mucosa pale fluorescence in the blue-green spectral region. The precancerous mucosa also revealed a red light signal, but with lower intensity levels than the carcinoma lesions observed in situ . False-positive signals were recognized in case of inflammations in the colon and rectum areas, where 5-ALA/PpIX was accumulated as well.